Study on Oil Flow Surging and Protection Optimization for on Load Tap Changer of Converter Transformer - Zhou, Haibin; Xie, Zhicheng; Chen, Xing; Guan, Qinggang; Deng, Jun; Liu, Guanwei; Yan, Xiaojiang (Frontiers in Energy Research, 2022)
The on-load tap-changer (OLTC) is one of the key components of converter transformer, the energy generated during tap switching process of OLTC will cause the thermal expansion and surging of insulating oil in the chamber, resulting in the mis-operation of protective relay, and threatening the safe and stable operation of the power system as well. Therefore, taking the typical dual transition resistance type OLTC as an example, a numerical modeling method of OLTC oil flow surging based on the Realizable k-ε model is proposed, and the fluid simulation model is established based on FLUENT software. The quantitative relationship between OLTC transition resistance value and the oil velocity and oil pressure at the top of the oil chamber is analyzed, that is, the smaller the transition resistance, the greater the oil flow velocity and oil pressure during switching. In addition, the equivalent experimental platform is built to carry out the static action characteristic experiment of OLTC oil flow relay, the corresponding relationship between the change range of oil pressure at the top of the chamber and the oil velocity under typical value (1.5m/s, 2.0m/s, 2.5m/s) are revealed. Based on which, the optimization suggestions on the protection relay threshold configuration of OLTC oil velocity and oil pressure are put forward.